Rheumatoid Arthritis and Cardiovascular Risk: Retrospective Matched-Cohort Analysis Based on the RECORD Study of the Italian Society for Rheumatology - Argnani, Lisa; Zanetti, Anna; Carrara, Greta; Silvagni, Ettore; Guerrini, Giulio; Zambon, Antonella; Scirè, Carlo Alberto (Frontiers in Medicine, 2021)
Background. Rheumatoid arthritis (RA) is associated with an increase in cardiovascular risk (CV). This issue may be not only explained by traditional CV risk factors, but also by an underestimation of concomitant CV comorbidities, as well as their suboptimal management. Method. This was a retrospective matched-cohort analysis in Italian RA real-world population based on healthcare-administrative databases to assess CV risk factors and incidence of CV events in comparison with the general population. Persistence and adherence to CV therapy were also evaluated in both groups. Results. In RA cohort (N=21,201) there was a greater prevalence of hypertension and diabetes with respect to non-RA subjects (N=249,156) (36.9% versus 33.4% and 10.2% versus 9.6%, respectively), while dyslipidemia was more frequent in the non-RA group (15.4% versus 16.5%). Compared to non-RA cohort, RA patients had a higher incidence of atrial fibrillation (incidence rate ratio, IRR 1.28), heart failure (IRR 1.53), stroke (IRR 1.19) and myocardial infarction (IRR 1.48). RA patients presented a significantly lower persistence rate and lower adherence to glucose-lowering treatments than controls (odds ratio, OR 0.73 [95%CI 0.6-0.8] and OR 0.70 [0.6-0.8], respectively). No statistically significant differences emerged regarding the adherence to lipid-lowering therapy (OR 0.89 [95%CI 0.8-1.0]) and anti-hypertensive therapy (OR 0.96 [95%CI 0.9-1.0]). Conclusion. RA patients have a higher risk of developing CV events compared to the general population, which may partially explain by undertreatment of CV risk factors.